DOCTORS' PREFERENCE FOR SPINAL ANESTHESIA FOR CHOLECYSTECTOMY - Rehab Sabah Abd-Alhussein Otaifa; Dr. Reem Hashim Abdalmahdi Shuber; Dr. Sudad Mohammed Salih AL Haddad (Scholar Express Journals, 2022)
Laparoscopic cholecystectomy under spinal anaesthesia has been reported, as 100 patients were collected from different Hospitals in Iraq. The aim of the research is to find out whether spinal anaesthesia is safe and why doctors prefer spinal anaesthesia; All these reports included patients suffering from cholelithiasis, and the statistical analysis program SPSS SOFT AND MS EXCEL was relied on. We have shown in a pilot study that successful and safe laparoscopic cholecystectomy with low-pressure CO pneumoperitoneum is possible under spinal anaesthesia alone and mild symptoms were found. We also found that spinal anaesthesia results in exceptionally minimal postoperative pain. After this study, we conclude from this research that spinal anaesthesia is safe and preferable compared to standard general anaesthesia for laparoscopic cholecystectomy in suitable patients
Keywords: Anaesthesia; cholecystectomy; spinal; pneumoperitoneum